Bimbingan Teknis Optimalisasi Penggunaan Residu Maggot sebagai Bahan Baku dalam Pengolahan Pupuk Organik - Sucipto, Irwanto; Muhlison, Wildan; Anggriawan, Rendy; Candra Setiawati, Tri; Dwi Maharani, Ariq (Program Studi Ilmu Tanah, Fakultas Pertanian, Universitas Jember, 2024)
Organic waste is one of the main environmental problems in many countries, including Indonesia, where its presence can cause ecosystem imbalance. Utilizing insects in the agricultural production cycle is a potential alternative for producing valuable protein feed and sustainable organic fertilizer. This community service program aims to provide technical guidance on using maggot residue as a raw material for processing organic fertilizer. The implementation of this community service program consists of several stages, including preparation, planning, execution, and evaluation. The execution stage involves multiple activities, such as field visits, material presentations, and practical fieldwork. The outcome of this technical guidance includes increased literacy and understanding among maggot breeders and horticultural farmers regarding the use of maggot residue as a raw material in organic fertilizer processing. The decomposition of waste by BSF larvae yields better results due to its higher nutrient content. The residual waste decomposed by BSF larvae can be transformed into compost with high benefits and can be applied to cultivated plants or soil to improve soil properties.